2012
DOI: 10.1111/j.1529-8019.2012.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of neutrophilic dermatoses

Abstract: Neutrophilic dermatoses, including Sweet's syndrome, pyoderma gangrenosum, and rheumatoid neutrophilic dermatitis, are inflammatory conditions of the skin often associated with underlying systemic disease. These are characterized by the accumulation of neutrophils in the skin. The associated conditions, potential for systemic neutrophilic infiltration, and therapeutic management of these disorders can be similar. Sweet's syndrome can often be effectively treated with a brief course of systemic corticosteroids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 166 publications
(148 reference statements)
1
19
0
Order By: Relevance
“…In addition to the two major criteria (abrupt onset of tender or painful erythematous or violaceous plaques or nodules and neutrophilic infiltration of the dermis without leukocytoclastic vasculitis), he had three minor criteria (elevation of the CRP level, leukocytosis and preceding slight fever) [2]. Like our case report, cases of SS with recurrent oral ulcerations were reported [1,[4][5][6][7]. They had tender erythematous nodular or vesicle-like papular skin eruptions on both forearms [5], over the face, neck, palms and legs [4], multicentric erythema and pustules progressing to ulcers on the legs, face, trunk and extremities [7], and erythematous plaques on the legs [6].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In addition to the two major criteria (abrupt onset of tender or painful erythematous or violaceous plaques or nodules and neutrophilic infiltration of the dermis without leukocytoclastic vasculitis), he had three minor criteria (elevation of the CRP level, leukocytosis and preceding slight fever) [2]. Like our case report, cases of SS with recurrent oral ulcerations were reported [1,[4][5][6][7]. They had tender erythematous nodular or vesicle-like papular skin eruptions on both forearms [5], over the face, neck, palms and legs [4], multicentric erythema and pustules progressing to ulcers on the legs, face, trunk and extremities [7], and erythematous plaques on the legs [6].…”
Section: Discussionsupporting
confidence: 63%
“…Neutrophilic dermatoses (ND) are a collection of diseases characterized by the accumulation of neutrophils in the skin without an identifiable infectious agent [1]. Neutrophilic dermatoses, including Sweet's syndrome (SS), pyoderma gangrenosum (PG), subcorneal pustular dermatosis (Sneddon-Wilkinson disease (SW)) and rheumatoid neutrophilic dermatitis, are inflammatory conditions of the skin often associated with underlying systemic disease [2].…”
Section: Introductionmentioning
confidence: 99%
“…SS recurs in approximately one-third of patients. Of the cases that recur, the cause is often malignancy or drug induced 3 4. Although there were four cardinal features of SS when first described, further reports reveal that fever and neutrophilia were not consistent features.…”
Section: Discussionmentioning
confidence: 99%
“…Second-line therapies include nonsteroidal anti-inflammatory drugs (e.g., indomethacin, naproxen), dapsone, clofazimine, cyclosporine, and thalidomide. There are reports of efficacy with methotrexate, danazol, interferon-alpha, intravenous immunoglobulins, and etetrinate [17]. Lucia et al reported successfully using rituximab for recalcitrant SS [19], but further studies are required to definitely suggest it as a treatment.…”
Section: Discussion:-mentioning
confidence: 99%
“…Corticosteroid therapy is considered first-line treatment for SS [16]. In addition, there are some reports suggesting the use of colchicine and potassium Iodide as first-line treatment options [17]. Symptoms often begin to improve within 48 hours and skin lesions usually resolve within one to two weeks after use of steroids [18].…”
Section: Discussion:-mentioning
confidence: 99%